THE GOVERNMENT CONTRACTUAL DISPUTE RESOLUTION TRUTH INTERNATIONAL COMMERCIAL ARBITRATION AND ITS PROBLEMS - M. Yazid Fathoni2, Diangsa Wagian1 (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
The research aims to study legal issues that appear within the government contractual disputeresolution through international commercial arbitration. The research is a legal normative.Therefore, it simultaneously applies to statute, conceptual, and case approaches. This literature research is conducted towards regulations, court decisions, legal books and legal journals that relate to the government contractual dispute resolution through international commercial arbitration. The results of the research elaborated in a descriptive and analytic way using qualitative methods to analyze the data. The research discovers that the presence of the government before the international commercial arbitration to settle disputes with foreign investors brought up some legal issues. Among others these are: a) state (government), through the law of limited company, this potentially reduces the jurisdiction of the ICSID Centre to settle foreign investment disputes between state and foreign investors; b) Courts as shown in some cases, block the enforcement of the foreign arbitration award which inflicts financial loss for state (government); c) the involvement of a state legal entity (state enterprise) ends in the engagement of state (government) as parties within the foreign investment dispute face to face with investors in front of a foreign justice court; and d) the unwillingness of state enterprise to perform the foreign arbitration award makes state assets overseas vulnerable to be confiscated by foreign investors as collateral in their claim for damages.Key Words: Government Contract, Contractual Dispute, Dispute Resolution, InternationalCommercial Arbitration.